Ethnomedicinal Plant Terong Pungo (Solanum sp.) - LINAWATI HARDJITO (Microbiology Indonesia, 2008)
The leaf of terong pungo Solanum sp. had been used traditionally in Aceh to treat toothache and relieve pain. Based on traditional knowledge, this research was conducted to examine the biological activities of its extract as an antibacterial agent and topoisomerase-I inhibitor. The topoisomerase-I inhibitor is one of the target molecules for anticancer compounds. In addition, it is also a target molecule for antimicrobial compounds. The antibacterial activity was examined using disc diffusion assay against Staphylococcus aureus and Escherichia coli isolated from medical patients. Topoisomerase-I inhibitor activity was determined using the method reported by TopoGEN, and its toxicity was examined against Artemia salina. Chloroform, ethyl acetate, and methanol treatments yielded crude extracts of 1.44, 1.20, and 2.69%, respectively. The chloroform extract exhibited neither antibacterial nor topoisomerase-I inhibitor activities, while the ethylacetate and methanol extracts at a concentration of 300 μg/paper disk positively inhibited the growth of both target bacteria or enzyme activity of topoisomerase-I at a concentration of 50 μg ml-1. The ethylacetate extract showed better activity against target bacteria and was chosen for further investigation. The results suggest that the crude extract showed antibacterial and topoisomerase-I inhibitor activity. Identification of the isolated active fraction indicated that it contained a steroidal alkaloid compound. This investigation revealed that the leaf of terong pungo contains biologically active compounds of pharmacological relevance.